Discontinuation of affirmative action: Consequences for black educational equity, neurosurgical residency, and medical diversity, with consideration of potential adversity as a new path forward - Albert Alan; Michelle Ennabe; Abdulmuizz Sulaiman; Martin Weinand (World Neurosurgery: X, 2024)
Background: The underrepresentation of the Black community in neurosurgery is concerning, especially given projections that racial minorities will become the majority in the U.S. by 2044. Yet, despite these forecasts, Black candidates make up less than 4% of those in neurosurgical training programs. The recent Supreme Court decision to end Affirmative Action underscores the urgency of addressing this disparity. This research delves into the implications of eliminating Affirmative Action on neurosurgery admissions and residencies. Methods: A comprehensive literature search was performed using PubMed, OVID Embase, and OVID Medline, employing the keywords “Black”, “Neurosurgery”, and “Residency”. The Maslow Adversity Index (MAI) was created to integrate adversity as a factor in neurosurgery residency evaluation. Results: After Affirmative Action, Black college enrollment increased, peaking at 36% by 2020. However, Black medical students remain underrepresented in neurosurgery residencies. ALDC (Athletes, Legacies, Dean’s List, Children of faculty/staff) admissions criteria favor White students. Furthermore, studies have highlighted the beneficial impacts of racial concordance on patient outcomes. The end of Affirmative Action necessitates new diversity strategies in admissions. A points-based assessment, inspired by Maslow's hierarchy, recognizes adversities faced by underrepresented applicants which could help residency programs enhance diversity, inclusivity, and equity in selection. Conclusion: Despite the growth in Black college attendance, disparities persist in specialized medical fields like neurosurgery. The end to Affirmative Action policies might exacerbate these disparities. Embracing holistic admission approaches, rooted in Maslow's hierarchy. This consideration is key for inclusive representation, impacting education, professions, and health outcomes.